The effects of dosing feedlot cattle with Megasphaera elsdenii strain NCIMB 41125 prior to the introduction of a grain-rich diet - McDaniel, Michael Reid (Kansas State University, 2009)
Two experiments were conducted to evaluate the efficacy of [italic]Megasphaera elsdenii[italic] strain NCIMB 41125 and its potential use in the mitigation of ruminal acidosis. In experiment 1, a metabolism study was conducted to evaluate ruminal parameters, quantify changes in ruminal bacterial populations, and determine in vitro capacity for lactate utilization following intraruminal dosing of a placebo or [italic]M. [italic]elsdenii strain NCIMB 41125 and an abrupt diet change. Angus crossbred steers (n=20; average BW=253 ± 24 kg) fitted with ruminal cannulas were blocked by BW and assigned randomly to treatments. Treatments consisted of intraruminal dosing with a placebo (100 mL of autoclaved culture), or 10, 100, or 1,000 mL of a live culture containing 1.62×108 CFU/mL of [italic]M. elsdenii[italic] strain NCIMB 41125. Prior to inoculation, cattle were placed into individual pens in an enclosed facility and allowed free access to alfalfa hay, salt, and water. Feed and water were removed for 24 h prior to administering treatments, after which, cattle were allowed free access to a diet consisting of 34% alfalfa hay and 66% steam-flaked corn-based concentrate. On d 7, cattle were fed an 80% concentrate diet. On d 12, steers were started on the final finishing diet of 94% concentrate. Ruminal pH and concentrations of lactate and VFAs were monitored following introduction of each concentrate diet. Ruminal samples were collected at 0, 2, 4, 6, 8, and 24 h after feeding for quantitative rt-PCR detection of native and introduced strains of [italic]M. elsdenii[italic], as well as total bacterial genomes. Capacity for metabolism of lactic acid was evaluated by inoculating 0.2 mL of strained ruminal fluid into anaerobic culture tubes containing 15 mL of semi-defined lactate medium. Tubes were incubated at 39˚C, and turbidity changes were determined by measuring absorbance at 2 h intervals up to 12 h. Experiment 2 was conducted in a commercial feedlot to evaluate the efficacy of [italic]M. elsdenii[italic] strain NCIMB 41125 for improving feedlot performance. A second objective of the study was to determine if oral dosing of [italic]M. elsdenii[italic] has the potential for reducing the number of cattle treated for bovine respiratory disease. Angus steers and heifers (n = 3179; average BW = 356 ± 58.4kg) were used in a randomized complete block design with two treatments. Cattle were assigned to treatment on an every-other-head basis such that every-other-animal was orally drenched with 100 mL of a culture medium containing 1.5×108 cfu/mL [italic]M. elsdenii[italic] strain NCIMB 41125 at processing. Cattle were blocked by gender and date of arrival. To maximize profitability, cattle were sorted via visual appraisal to identify cattle that were market ready. Cattle were shipped to a commercial abattoir in Lexington, NE for harvest. Data obtained for each pen of cattle included feedlot performance, morbidity, mortality, carcass characteristics, and grid-based program carcass qualifications. In trial 1, compared to the placebo group, cattle administered [italic]Megasphaera[italic] maintained higher ruminal pH 24 h after the carbohydrate challenge (P < 0.05). Ruminal lactate concentrations increased in response to the diet change (P < 0.05), but concentrations were lower for cattle that received [italic]Megasphaera[italic] compared to the placebo group (P < 0.05). Total number of bacterial genomes 24 h after inoculation was unaffected by intraruminal dosing of [italic]M. elsdenii[italic] strain NCIMB 41125 (P > 0.05), but populations of undifferentiated [italic]M. elsdenii[italic] and strain NCIMB 41125 increased by 24 h after inoculation (P < 0.05). Turbidity of cultures inoculated with ruminal fluid increased in response to [italic]M. elsdenii[italic] administration (P < 0.05), suggesting a greater capacity for lactate utilization in inoculated cattle compared to the placebo group. In trial 2, no differences in feed efficiency were observed (P > 0.05). Compared to cattle dosed with [italic]Megasphaera[italic], the control group had more USDA yield grade 2 carcasses (P < 0.05), and cattle dosed with [italic]M. elsdenii[italic] had more USDA yield grade 5 carcasses (P < 0.05). [italic]Megasphaera[italic] cattle also tended to have more USDA Prime carcasses (P = 0.14). No effects on incidence of liver abscesses were observed. Dosing cattle with [italic]M. elsdenii[italic] prior to introduction of typical concentrate diets may be useful in preventing ruminal lactate accumulation and associated depressions in ruminal pH. Inoculating cattle with [italic]M. elsdenii[italic] is effective in bolstering populations of ruminal lactate utilizers, and may be useful in preventing ruminal lactate accumulation in grain-fed cattle. No effects on reducing episodes of BRD were noted.
Keywords: Megasphaera elsdenii; Lactate; VFA; Acidosis; Feedlot; Cattle; Agriculture, Animal Culture and Nutrition (0475)